Diagnóstico da geração de resíduos de construção e demolição em etapas construtivas no município de Maringá/PR - Violin, Ronan Yuzo Takeda (2009)
This work describes construction and demolition waste (C & D waste) originated in building site, through analysis of them in the construction stages of engineer construction work and it will also use a check-list for inventory of C & D waste. C & D waste production can be identified by the alignment of projects, measures that turn theses residues down, C & D waste characterization and quantification of C & D waste production and it permits to indicate construction stages that show the biggest impact and need stronger control. In this study, four construction works at Maringá/PR works were studied, three of which possess traditional constructive system and other shows streamlined constructive system. In construction works studied, alignment of projects has had great results in construction works with lot of time to planning and with large buildings. Measures that turn C & D waste down were analyzed through check-list that allows creating graph determination of percentage of the each measure and material control. At the time of study, these construction works were in different stages of execution. Thus, some materials had more control in one building and in other, they were not use. Characterization C & D waste production was determined by materials which were used in each constructive stage and also by quantification of these materials. Therefore, it was generated C & D waste percentage in each stage. C & D waste quantification was studied by C & D waste volume in lorries which collect these materials. Each construction work C & D waste volume was multiplied for C & D waste percentage of each constructive stage, resulting C & D waste volume in each stage. In this research, construction and demolition residues volume had fluctuating, which is justified for construction stage in execution and necessity to demolition and site cleaning.